Difference of flavor characteristics and microbial community of normal and urn odor of red sour soups and correlation analysis - HE Yangbo, LI Guolin, SHI Bin, LI Wei, LI Yongfu, ZHENG Ruzhong, ZHU Ting, YANG Yi (Zhongguo niangzao)
In this study, the sensory quality, volatile flavor components and microbial communities of normal flavor (LSN) and urn odor (LS42, LS44 and LS143) red sour soups were determined using electronic nose, electronic tongue, gas chromatography-mass spectrometry (GC-MS) and high throu- ghput sequencing technology. Possible sources of undesirable flavors and their correlations with microorganisms were analyzed using aroma activity values (OAV). The results showed that the taste richness of the urn odor red sour soup was stronger, but its sour, salty, and fresh flavors were weaker than those in normal samples. A total of 138 volatile flavor compounds were detected in the red sour soups, and the types and contents of esters, alkenes and alcohols were absolute dominant, accounting for 91.19%, 85.77% and 91.22% of all volatile substances in samples LSN, LS42 and LS143. Compared with the normal samples, the short-chain fatty acids with odor such as n-valeric acid (13.599 μg/g) and butyric acid (7.319 μg/g) were detected in the sample LS143, and their OAV was greater than 1, which contributed significantly to flavor. Rhodobacter sp. 001617365, Lactobacillus acetoolerans, Sediminibacterium magnilica habituans, Bradyrhizobium sp. 000938305, Limosilactobacillus oris, and Brettanomyces custersianus were potential contributing microorganisms to the normal flavor of red sour soup. Chitinophaga vietnamensis, Mesohizobium terrae, and Rhodobacter sp. 001617365 were positively correlated with butyric acid, valeric acid, etc., which might be one of the main factors causing the urn odor of red sour soup.